2020
DOI: 10.3390/fermentation6010015
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of Phenolic Compounds, Biogenic Amines, and Volatile Compounds in Cabernet Gernishct Wine through Malolactic Fermentation by Lactobacillus plantarum and Oenococcus oeni

Abstract: Malolactic fermentation is a vital red wine-making process to enhance the sensory quality. The objective of this study is to elucidate the starter cultures’ role in modifying phenolic compounds, biogenic amines, and volatile compounds after red wine malolactic fermentation. We initiated the malolactic fermentation in Cabernet Gernishct wine by using two Oenococcus oeni and two Lactobacillus plantarum strains. Results showed that after malolactic fermentation, wines experienced a content decrease of total flava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 84 publications
1
9
0
1
Order By: Relevance
“…The differences in volatile acidity and anthocyanin observed after AF were not maintained at this time. Comparing both moments, it can be seen that during the MFL there was a decrease in all the parameters involved in the color of the wine, as other authors had previously indicated [48].…”
Section: Physicochemical Characteristics Of Winessupporting
confidence: 66%
See 1 more Smart Citation
“…The differences in volatile acidity and anthocyanin observed after AF were not maintained at this time. Comparing both moments, it can be seen that during the MFL there was a decrease in all the parameters involved in the color of the wine, as other authors had previously indicated [48].…”
Section: Physicochemical Characteristics Of Winessupporting
confidence: 66%
“…MLF is an important red winemaking process after AF since it can significantly improve the quality of red wine [48] enhancing the aromatic complexity of wine via LAB metabolism. Our results showed that during the MLF all the wines had a significant decrease (p ≤ 0.05) of acetaldehyde, and significant increase in octanoic acid, ethyl lactate, methionol, acetoin, diacetyl, and butyrolactone (statistical results not shown), which supposed a greater aromatic complexity of the wines.…”
Section: Aromatic Composition Of Winesmentioning
confidence: 99%
“…Or some glucosides can suffer hydrolysis reactions for this change in pH [ 25 ]. Moreover, malolactic fermentation provides microbiological stability and improves the final aroma balance by modifying fruit-derived aromas and producing aroma-active compounds [ 26 , 27 , 28 ].…”
Section: Polyphenols: Key Compounds For Wine Qualitymentioning
confidence: 99%
“…The adaptability of L. plantarum to a fermentation process and its metabolic flexibility and versatility are some of the critical attributes, that makes it unique among the other LAB [63]. L. plantarum has been isolated through numerous food sources, such as cereals, meats, dairy products, vegetables, fruits and drinks [64][65][66][67][68], as well as human and mammals niches [69]. L. plantarum can adapt to various niches, probably due to its genome size (average 3.3 Mb), which is one of the largest detected within Lactobacillus genus [70].…”
Section: Main Advantages Of L Plantarum Application In Food Fermentationsmentioning
confidence: 99%